Patient Satisfaction in Relation to Esthetic Outcome of Dental Treatment: A Systematic Review and Pooled Analysis - Agarwal, Bhaskar; Srivastava, Shitij; Shekhar, Abhinav; Arora, Kshitij (Journal of interdisciplinary dentistry, 2023)
ABSTRACT Introduction: Esthetics is often an essential yet ignored aspect of dental treatment. In the present study, an attempt was made to evaluate patient satisfaction in terms of esthetic outcome of dental treatment. MaterialS and Methods: For this purpose, a systematic review was carried out by searching, MEDLINE, PubMed, and Scopus databases using the keywords "esthetics," "orthodontic treatment need," "dental treatment need," "satisfaction," and "determinants." A total of 1075 studies were shortlisted, out of which a total of 927 were excluded in the preliminary assessment itself. A further 779 were excluded during the process of identification of themes and concepts and another 73 were out of sampling frame/inappropriate methodology. Of the remaining 75, a total of 44 studies were related with expectation and perceptions and thus only 31 (2.9%) studies were left that had evaluated esthetics as the treatment outcome. Among these, 9 studies each were related with orthodontic and prosthodontic/implantology treatment, respectively, while 6 studies were related with general dental treatment, and the remaining 7 were related with specialized/esthetic procedures. Results: The overall patient satisfaction rate was 67.3%. It was highest in the prosthodontics and dental implantology group (75.1%) and lowest in patients availing of generalized dental (32.4%). Conclusion: Patient satisfaction was affected by gender, pretreatment appearance, patient personality characteristics, type of disorder, patient education, previous bad experience, treatment time, cost of treatment, use of appliance/treatment modality/material, practice location and environment, dentist personality, quality of treatment, patient's esthetic perception, negligence/regularity, smoking, and oral health factors. CLINICAL RELEVANCE TO INTERDISCIPLINARY DENTISTRY The article targets to describe the patient expectations with respect to esthetic dental treatment and how patient's satisfaction is affected by different esthetic dental treatments availed by them for various purposes. The article also highlights the various dental treatment options availed by the patients and their esthetic outcome.